Hepatitis B Virus Vaccination in HIV-1-Infected Young Adults: A Tool to Reduce the Size of HIV-1 Reservoirs? - Bekele, Yonas; Graham, Rebecka Lantto; Soeria-Atmadja, Sandra; Nasi, Aikaterini; Zazzi, Maurizio; Vicenti, Ilaria; Naver, Lars; Nilsson, Anna; Chiodi, Francesca (Frontiers in Immunology, 2018)
During anti-retroviral therapy (ART) HIV-1 persists in cellular reservoirs, mostly represented by CD4+ memory T cells. Several approaches are currently being undertaken to develop a cure for HIV-1 infection through elimination (or reduction) of these reservoirs. Few studies have so far been conducted to assess the possibility of reducing the size of HIV-1 reservoirs through vaccination in virologically controlled HIV-1 infected children. We recently conducted a vaccination study with a combined Hepatitis A virus (HAV) and Hepatitis B Virus (HBV) vaccine in 22 HIV-1 infected children. We assessed the size of the virus reservoir, measured as total HIV-1 DNA copies in blood cells, prior and after completed vaccination. In addition, we investigated by immunostaining whether the frequencies of CD4+ and CD8+ T cells and parameters of immune activation and proliferation on these cells were modulated by vaccination. At one month from the last vaccination dose, we found that 20 out of 22 children mounted a serological response to HBV; a majority of children had antibodies against HAV at baseline. The number of HIV-1 DNA copies in blood at 1 month post-vaccination was reduced in comparison to baseline although this reduction was not statistically significant. A significant reduction of HIV-1 DNA copies in blood following vaccination was found in 12 children. The frequencies of CD4+ (Naïve, effector memory) and CD8+ (central memory) T cell subpopulations changed following vaccinations and a reduction in the activation and proliferation pattern of these cells was also noticed. Multivariate linear regression analysis revealed that the frequency of CD8+ effector memory T cells prior to vaccination were strongly predictive of the reduction of HIV-1 DNA copies in blood following vaccination of the 22 HIV-1 infected children. The results of this study suggest a beneficial effect of vaccination to reduce the size of virus reservoir in HIV-1 infected children receiving ART. A reduced frequency of activated CD4+ cells and an increase in central memory CD8+ T cells were associated with this finding. Further studies should assess whether vaccination is a possible tool to reduce HIV-1 reservoirs.